Answer:
1. n = 1/2
2. m = 5/3 or 1 2/3
3. a = 1/4
4. x = 27/8
5. x = 13/6
Explanation:
I'm just going to explain step 5 as that is what you specifically needed help with.
First, simplify the second term of the equation:
-6(2.5x-3)
= -15x + 18
(this was done by multiplying -6*2.5x which is 15x and -6(-3) which is 18)
Now, add this simplified second term back to the first term:
3x + 8 - 15x + 18
(the parentheses are unnecessary now because it is all just addition and subtraction, so the order doesn't matter)
Simplify:
-12x + 26 = 0
= -12x = -26
= x = -26/-12
= x = 13/6